1994
DOI: 10.1089/cbr.1994.9.211
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Tumor Derived Activated T-Cells for the Treatment of Cancer

Abstract: This report describes the production of Tumor Derived Activated Cell cultures (TDAC, also called tumor infiltrating lymphocytes) from patient tumor biopsies and our preliminary experience growing these cells to therapeutic levels using artificial capillary bioreactor cultures. TDAC were successfully grown in medium containing Interleukin 2 from 80% of the 113 tumor biopsies tested. There was no significant difference in success (growth to 1 x 10(9) cells) comparing primary and metastatic tumors. Many of the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This report is in follow-up to an earlier report encompassing the years 1991-1995 during which time TIL were initiated in T-flasks but were expanded using only 3L-gas permeable culture bags. 10 The overall success rate for initiation of TIL in this series is 76%, which is comparable to the success rate of 71% in our previous series, and comparable to the success rates reported by ourselves and other investigators 7,9,10,14,15 including another recent report using bioreactors. 25 We used the TIL expanded by bioreactor for a 111 Indium labeled TIL study that showed specific trafficking to tumors in patients with melanoma, renal cell carcinoma, and colon cancer.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This report is in follow-up to an earlier report encompassing the years 1991-1995 during which time TIL were initiated in T-flasks but were expanded using only 3L-gas permeable culture bags. 10 The overall success rate for initiation of TIL in this series is 76%, which is comparable to the success rate of 71% in our previous series, and comparable to the success rates reported by ourselves and other investigators 7,9,10,14,15 including another recent report using bioreactors. 25 We used the TIL expanded by bioreactor for a 111 Indium labeled TIL study that showed specific trafficking to tumors in patients with melanoma, renal cell carcinoma, and colon cancer.…”
Section: Discussionsupporting
confidence: 88%
“…However, this technique required significantly longer periods of cultivation time to achieve therapeutic levels, as compared to the single cell technique, approximately 78 days on the average. 7 Also, like the single cell concept, expansion of the TIL involves significant technical time and incubator space as a large number of flasks and/or bags are required to achieve a therapeutic dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative cell culture technology is the hollow-fiber bioreactor, first discribed by Knazek et al (1). With this technology it is, in principle, possible to overcome some limitations of monolayer cultures, to realize increased cell densities and concentrations of secreted effector molecules (2)(3)(4), and to permit a continuous cell cultivation process approaching tissue-like cell densities (5). Most hollow-fiber bioreactors are similar in design and size to modules used in hemodialysis of uremic patients (6).…”
Section: Introductionmentioning
confidence: 99%